A revised free space path loss (FSPL) formulation for satellite link operating in tropical region - Badron, Khairayu; Ismail, Ahmad Fadzil; Basri, Atikah Balqis (2019)
Adequate fade margins for all conditions are critical in ensuring reliable satellite operation. The required fade margin value for the specific desired quality of service (QoS) can be established from the statistics of outage due to attenuation. More power margin is typically required in mitigating such problem. However, the solution is definitely not cheap. Alternatively, signal fade margin can be configured and be implemented in the attempt to increase system availability. This effort will help to reduce the greenhouse effect. In the case of clear sky attenuation, the value is much dependent on the atmospheric layer conditions and their compositions. For absolute Free Space, the signal loss is only dependent on distance and frequency. In this study, the effects of power, distance and frequency were analysed in the investigation of identifying the most appropriate clear sky attenuation. This can be achieved by designing, assemble and carried out empirical experimental set up to evaluate FSPL values to identify the variation between the theoretical and empirical values of the free space path loss at Electromagnetic Compatibility Chamber (EMC) room at Malaysian National Space Agency located at Banting Selangor. The development of revised formulation can be achieved. The clear sky conditions were confirmed using S-band (Terminal Doppler Weather Radar) TDWR reflectivity information acquired from Malaysian Meteorology department (MMD). Validation for the proposed revised free space path loss equation by using RazakSAT S-band (2.232 GHz) transmission signal data were furnished by the Malaysian National Space Agency (ANGKASA). The RazakSAT processed received signal level was taken into consideration by eliminating any possible signal variation due to atmospheric impairments (La). As a result, the revised free space path loss equation proposed the better FSPL value than the ITU-R proposed equation. This is certainly a great improvement as compared to ITU-R estimation. The findings of this research will be valuable for the future engineers in configuring the best communication establishment for satellite system operating in the tropics.